Exploration of Potential Reading Interest Groups in Social Sciences of Undergraduates Based on Social Network Analysis: A Case Study of China Pharmaceutical University - LI Pei, GU Donglei, ZOU Tao, JIANG Ling, LIU Jianfeng (Nongye tushu qingbao xuebao, 2021)
[Purpose/Significance] The government work report mentioned nationwide reading for six consecutive years, and reading promotion has been carried out in the whole society. As an important place to carry out the national reading programs, in the context of the rapid development of modern technologies, colleges and universities are in urgent need of innovative practice of reading promotion to adapt to the development of the times, so as to provide useful reference for the research and practice of accurate promotion of reading.[Method/Process] Based on the social network analysis technology, this paper downloads the book loan data of undergraduates from China Pharmaceutical University from Huiwen system, calculates the distribution status of the network with UCINET, and explores the potential reading interest groups of undergraduates in social sciences.[Results/Conclusions] The application of the social network analysis technology to the analysis of undergraduate reading data discovers a reading group with undergraduate interest as the core. On this basis, this paper puts forward the promotion strategy of accurate reading, proposes the establishment of the complex network theory to mine the potential reading team model, and studies the internal dynamic mechanism of undergraduate reading teams.